Analysis Of Factors That Affect The Auditors’ Audit Judgment (A Case Study At The Audit Board Of The Republic Of Indonesia BPK RI - Wulan Wahyuni Rossa Putri; Sudradjat Sudradjat; Jasmadeti Jasmadeti (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2020)
The purpose of this study is to analize factor – factor such as auditor experience and obedience pressure can be influence to audit judgment. This research is quantitative research, the data used in this study is primary data by distributing questionnaires to BPK Jakarta. Data is processed using the help of SPSS 25. Population in this study were auditor who work in the BPK Jakarta. Questionnaires were distributed as many as 202 questionnaires, The samples selected by purposive sampling. The data analysis used methods to prove the hypothesis are classic assumptions test, multiple regression models. This Study result that auditor experience has no effect on audit judgment, but obedience pressure has a significant effect on audit judgment.